2004
DOI: 10.1093/qjmed/hch024
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention for coronary artery disease

Abstract: Secondary prevention measures are improving, especially in prophylactic prescribing, lipid management and smoking cessation, although scope for further improvement remains. No difference was seen between the patient subgroups. Lifestyle measures need to be addressed to gain maximum benefit in addressing overall cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…First, these patients have a greater baseline absolute risk and thus small differences in relative risk may be important. Second, approximately 90% of such patients take low dose aspirin, 37,38 which may interact with the NSAID. Third, either recent episodes of acute disease (eg, myocardial infarction) or disease treatment (eg, percutaneous interventions) may alter the cardiac safety of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, these patients have a greater baseline absolute risk and thus small differences in relative risk may be important. Second, approximately 90% of such patients take low dose aspirin, 37,38 which may interact with the NSAID. Third, either recent episodes of acute disease (eg, myocardial infarction) or disease treatment (eg, percutaneous interventions) may alter the cardiac safety of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…For similar reasons, misclassification of low-dose aspirin use also is likely for the North American sites, although the practical effect of such misclassification should be limited given that an estimated 90% of the cohort will be using low-dose aspirin. 37,38 Hence, the comparisons with naproxen are important, as these misclassification effects should be reduced for between-NSAID comparisons.…”
Section: Ray Et Al Nsaids In Serious Coronary Heart Diseasementioning
confidence: 99%
“…those reported in a recent survey of outpatients (97%, 59% and 80%) [7]. Most patients had a lipid profile measured and were successively prescribed a corresponding therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Over the last few years several studies have demonstrated clear improvements in the pharmacological prevention of coronary artery disease [5][6][7]. However, the targets are still not met and the most evident gaps may be found in older people, women, outpatients and diabetics [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation